Nutrigenomic and Biomolecular Aspect of Moringa oleifera Leaf Powder as Supplementation for Stunting Children - Agus Indra Yudhistira Diva Putra; Nyoman Budhi Wirananda Setiawan; Made Indira Dianti Sanjiwani; Ida Ayu Ika Wahyuniari; Agung Wiwiek Indrayani (Universitas Gadjah Mada, 2021)
Stunting is a global health problem. Based on WHO data, there are 161 million children who experience stunting. Breastmilk supplementation in the form of Moringa oleifera leaves powder is known to be beneficial in suppressing the stunting incidence. Moringa oleifera leaves powder contains protein, micronutrients, and minerals such as calcium, iron, sodium, vitamins C and E, beta carotene, and antioxidants (flavonoid acids, phenolic acids, glucosinolates, isothiocyanates, and saponins). The use of Moringa oleifera leaves powder in stunting cases has been carried out, but further studies in the aspects of nutrigenomics and molecular biology have not been conducted. This study is a literature review of relevant articles from www.pubmed.com, www.sciencedirect.com, and scholar.google.com. The author used keywords